DIGITALISASI KOLEKSI PERPUSTAKAAN SEBAGAI UPAYA MODERNISASI LITERASI SEKOLAH DASAR - Misroni; Zakiah Ayu Maytara; Mazhaya Naifa Maheswari Prayitno (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
In this digital era, libraries no longer only function as a place to store and borrow physical books, but also as a source of digital information that can be accessed via the internet. By digitizing library collections, students can access e-books, electronic journals, and various other digital information sources that can support the teaching and learning process in elementary schools. The design of this study is a Literature Review. In an effort to modernize literacy in elementary schools, it is important to increase the use of digital library collections. Effective strategies to achieve this can include training teachers and students in the use of digital libraries, developing interesting and relevant digital content, and increasing the accessibility and availability of digital library collections. By implementing this strategy, it is hoped that it can increase students' interest in reading and digital literacy so that they can be better prepared to face the increasingly developing digital era.